2007
DOI: 10.1074/jbc.m703676200
|View full text |Cite
|
Sign up to set email alerts
|

Phospholemman Transmembrane Structure Reveals Potential Interactions with Na+/K+-ATPase

Abstract: Phospholemman (PLM) is a 72-residue bitopic cardiac transmembrane protein, which acts as a modulator of the Na ؉ /K ؉ -ATPase and the Na ؉ /Ca 2؉ exchanger and possibly forms taurine channels in nonheart tissue. This work presents a high resolution structural model obtained from a combination of site-specific infrared spectroscopy and experimentally constrained high throughput molecular dynamics (MD) simulations. Altogether, 37 experimental constraints, including nine long range orientational constraints, have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 38 publications
3
10
0
Order By: Relevance
“…The data are compatible with a mixture of monomers and tetramers. That the major oligomeric species is a tetramer was previously suggested by in vitro experiments of another group (15,16,26) and is consistent with our own observation (in FRET experiments) that the oligomer size is three or more protomers (18). We found that the concentration of tetramers increased with average fluorescence intensity (Fig.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The data are compatible with a mixture of monomers and tetramers. That the major oligomeric species is a tetramer was previously suggested by in vitro experiments of another group (15,16,26) and is consistent with our own observation (in FRET experiments) that the oligomer size is three or more protomers (18). We found that the concentration of tetramers increased with average fluorescence intensity (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…For the PLM oligomer, the average donor-acceptor separation distance was calculated from FRET max using a computational model of intra-oligomeric FRET (25) as described previously (20,23). This model assumes a ring-shaped arrangement of subunits, which we regard as the most likely geometry (26). For values of R Ն R 0 , FRET efficiency is strongly dependent on donor-acceptor separation distance and only weakly dependent on the number of subunits in the complex (25).…”
Section: Methodsmentioning
confidence: 99%
“…The structure of the protein would, at first sight, appear to favour the latter suggestion. However, a recent report suggests that phospholemman tetramers have the potential to form a hydrophilic pore which could accommodate taurine [118]. It can be predicted, on the basis of evidence gathered from functional investigations, that molecular studies could eventually reveal the existence of more than one system for osmosensitive taurine transport.…”
Section: Shennanmentioning
confidence: 99%
“…FXYD1 is highly expressed in skeletal muscle and has been demonstrated to have an important influence on sodium pump function (28)(29)(30). Studying the relationship between FXYD1 and HypoPP may yield an improved understanding of the mechanism of the disease.…”
Section: Discussionmentioning
confidence: 99%